INFORMATION MEDIA AS A PUBLIC COMMUNICATION IN FIRE MITIGATION IN SOUTH KALIMANTAN - Astinana Yuliarti; Erma Ariyani (Universitas Lambung Mangkurat, 2023)
South Kalimantan is one of the regions in Indonesia that has a high vulnerability to fire disasters. The Fire Disaster Management Agency is an agency that has a major role as an early warning system in the process of mitigating fire disasters in South Kalimantan. The purpose of this study was to determine the use of the five elements of communication according to Harold Laswell and information media as a public communication channel carried out by the Regional Disaster Management Agency/ Badan Penanggulangan Bencana Daerah (BPBD) of South Kalimantan. The research method used was a qualitative descriptive approach. The results show that in the process of mitigating fire disasters in South Kalimantan Province, the Regional Disaster Management Agency/ Badan Penanggulangan Bencana Daerah (BPBD) of South Kalimantan Province has carried out a public communication process by implementing all elements of communication and presenting Information Media as a communication channel through direct communication with the community in the area. disaster or using conventional communication channels such as leaflets, disaster pocketbooks as well as mass and digital media communication channels such as radio and social media